The Influence of Work Motivation and Leadership Impact to Employee's Jobs Satisfaction at PT. Era Asta Marin Nusantara (PT. EAMN) - A Case Study - ., Hendric; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2017)
Abstract - Basically human resource is the only resource which had important role to determine the growth of an organization or a company. Human Resource improves the company's bottom line with its knowledge of how human capital affects the success of organizational. Leaders with expertise in human resource strategic management participate in corporate decision making that underlies current staffing assessments and projections for future workforce needs based on business demand.The objective of this study was to analyze and determine: a) the effects of work motivation on employee performance satisfaction, b) the effect of the impact of leadership on employee satisfaction and c) the effects of motivation and leadership impact to the satisfaction of employee performance.The design of this study is descriptive research which describes the information and characteristics of the population or phenomenon being studied at PT. Era Asta Marin Nusantara (PT. EAMN). The description used for statistical calculations, whereas a survey investigation was conducted to measure the variable with the distribution of questionnaires with statement by using a five point Likert scale and interview. The method used to evaluate the results of the survey is multiple regression. Research is based on primary data which are collected from the respondents of PT. EAMN, and also using secondary data to support the information. In order to analyze samples that are used mainly as primary data, purposive sampling is used to determine the sample. Thus, the data were analyzed using correlation method. The results of this study will show that there is a positive and significant relationship between motivation and leadership impact on job satisfaction in PT. EAMN. In addition, this study provides a suggests recommendation as a business solution to improve employee performance for the betterment of the company in the future.Key words: Human Resources; Work motivation; Leadership; Job satisfaction.